Review on the influence of water quality on livestock production in the era of climate change: perspectives from dryland regions - Diriba Tulu; Feyisa Hundessa; Sileshi Gadissa; Tasisa Temesgen (Cogent Food & Agriculture)
Freshwater availability is seriously threatened by expanding water demand and contamination concerns, particularly in dryland regions worldwide. Furthermore, global climate change is increasing water salinity by altering the global supply of groundwater and surface water. The quality of animal water has a significant impact on livestock production, influencing several processes such as growth, metabolism, reproduction, and body temperature. Although animals can tolerate bad water quality better than humans, livestock can be harmed if chemicals are added to the water. The poor quality of drinking water can have an impact on livestock productivity and welfare; however, tolerance to low water quality varies by species, race, and environmental conditions. As a result, this review examined the influences of poor-quality water on livestock production and productivity in arid and semi-arid areas in an era of changing climate. Despite variations in adapted physiological parameters, blood hematology, biochemical, food, and water consumption, camels and goats adapt to high salt levels in desert regions. Small ruminants’ nutritional intake and performance, as well as their breathing rate and blood biochemistry concentrations, all decrease when the salinity of their drinking water increases. While research on small and resilient ruminant breeds that can survive high salinity levels is underway around the world, further study is needed to understand the water-resistant features of adapted livestock species and breeds, particularly in dry and salty places impacted by changing climate.